Biodynamics of Hepatitis C Virus in Haemodialysis Patients in Pahang - AM, Mohammed Saad; AM, Mohammed Imad; HH, Aini; MR, Seman (IIUM Medical Journal Malaysia, 2012)
Introduction: HCV infection is frequent in patients undergoing maintenance haemodialysis, with prevalence between 8 and 10%. Hepatitis C has an adverse effect on both patient and graft survival in those who get renal transplants. There are relatively scarce reports on the natural fluctuation in viral load level in patients on chronic haemodialysis. Materials and Methods: This is a longitudinal short-term three months study, where 27 chronic haemodialysis patients infected with known HCV genotypes were recruited from seven haemodialysis centres in Pahang. Serum samples were collected monthly, both pre- and post-haemodialysis sessions, over a period of three months. Viral RNA was extracted from serum using QIAamp Viral RNA Extraction kit (Qiagen). The HCV viral load was measured using one-step reverse transcriptase qPCR (Applied Biosystems) targeting the 5`HCV non-coding region (5’UTR). The serum α-IFN level was measured using commercial ELISA kit (Amersham, UK). Six biochemical liver function tests (AST, ALP, TP, albumin, ALT and TB) were also done for all pre-haemodialysis samples. Results: All patients showed persistent low level viral load that varied significantly over the study period (p = 0.001). HCV genotype 1 viral load was significantly higher than that of genotype 3. Conclusion: No apparent correlation could be recognized between the viral loads and the corresponding interferon-alpha levels which were detectable in only a few patients during the period of study.